The Experience of the Design of the Survey “The Configuration of Psychological Boundaries of Personality” - Karelin, Pavlo A. (Psychological Prospects Journal, 2017)
This article contains a consistent description of the construction and validation of  multiscale personal survey that is based on the author’s model of the configuration process of psychological boundaries of personality. In this publication the author analyzes some modern approaches to understanding of the phenomenon of psychological boundaries of personality along with current condition of testological achievements in this area. The empirical operational model of the configuration process of psychological boundaries of personality is proposed. Psychological boundaries are presented as functional organ of personality. The main characteristics of psychological boundaries of personality are operationally defined for the purpose of future research of boundaries through tests. The concept of the configuration process of psychological boundaries is explained. The author describes the concept of “psychological sub-space of personality” (the dimension of psychological space of personality) and the empirical procedure of discovering of psychological sub-spaces of personality which are mostly used in a dyad communication. The types and main stages of the configuration process of psychological boundaries of personality in interpersonal interaction are defined. The author gives an overview of certain psychometric procedures used in the design process of this survey. Two stages procedure of ensuring the content validity of the survey “The configuration process of psychological boundaries of personality” is described. Certain psychometric procedures of the design and correction of the scales of this survey are also given. The original content structure of the scales of this survey is described in details. The main scales of the survey and the way of their evaluation is given. The results of the approbation experiment and the statistical analysis are given. The author describes characteristics of the empirical sample of pilot-testing and the principles of its formation. Also the techniques and their order that provides face and discriminant validity along with credibility of the survey scales are given. The article proves the validity and credibility of the developed test. The author suggests areas of its application.Key words: personal survey, the configuration process of psychological boundaries of personality.